Development of Pop-up Book Mediafolding Symmetry and Rotating Symmetryfor Class III Students Basic School - Karlimah, Karlimah; Suryana, Yusuf; Hardianti, Dewi; Nur, Lutfi (International Conference on Elementary Education, 2020)
The use of media in the learning process is very helpful for students' understanding, but in mathematics learning especially the traveling material and the wide flat area the use of media is still rarely used. One of the media that can be used is the pop-up book media which is a form of book packed with a three-dimensional structure with a part that can be moved and played. Researchers developed a pop-up book media concept around and wide flat area for fourth-grade elementary school students. The method used is Design-Based Research (DBR) which goes through four stages including problem identification, prototype development, due diligence, and reflection to produce the final product. This research shows that; 1) the development of pop-up book media is made according to the curriculum as well as from predetermined indicators, 2) pop-up books are made using the canva application and printed on 260 gsm art paper A3 size, 3) the use of pop-up book media the circumference and area of the flat build area are suitable for use in the learning process, in terms of the results of validation and testing. Product trials were conducted at two schools, which were reviewed from students' responses and observations during learning. In the learning process students are very enthusiastic about learning using pop-up book media, this is indicated by the positive response to the pop-up book media with the results achieved 96.54% and 99.78%, 4) the final product of this study is in the form media pop-up book concept around and wide flat area that is suitable for use. From the results of the study popup, book media around and wide flat area for fourth-grade elementary school students is suitable for use in learning mathematics